Peningkatan Kualitas Pembelajaran PKn di Sekolah Dasar Melalui Model Pengajaran Bermain Peran - L. Heny Nirmayani (Edukasi: Jurnal Pendidikan Dasar, 2020)
This research is a classroom action research, carried out cycle by cycle until the difficulties found are resolved. The implementation of classroom action research is carried out in the following order (1) planning, (2) action implementation, (3) results, (4) reflection, and (5) planning revision. Pancasila and Citizenship (Civics) education in elementary schools is intended to instill a love for the country, increase the spirit of nationality, and form a national personality that is in accordance with the philosophy, view of life, ideology, and the foundation of the country, namely Pancasila. Civics are education about values whose target is not merely the transfer of knowledge but rather emphasizes the formation of attitudes. One of the appropriate models to use is a role-playing model that can lead to learning experiences, such as the ability to cooperate, be communicative, and interpret an event. Through role playing, students try to explore human relationships by demonstrating and discussing them, so that together students can explore feelings, attitudes, values, and problem solving strategies. Keywords: Quality, Role Playing Models and Citizenship